Effects of tributyrin and alanyl-glutamine dipeptide on intestinal health of largemouth bass (Micropterus salmoides) fed with high soybean meal diet - Zhao, Jianhua; Yang, Xin; Qiu, Zongsheng; Zhang, Rongfei; Xu, Hong; Wang, Ting (Frontiers in Immunology, 2023)
To investigate the effects of dietary tributyrin (TB) and alanyl-glutamine (AGn) on the intestinal health of largemouth bass (Micropterus salmoides) fed with high-level soybean meal (SM) diet, six isonitrogenous (41.36%) and isolipidic (10.25%) diets were formulated and fed to largemouth bass (initial body weight 25.5±0.5g) for 8 weeks. The two control diets contained 34.8% peanut meal (PM) and 41.3% SM, while the other four experimental diets supplemented TB at 0.1% (TB0.1), 0.2% (TB0.2) and AGn at 1% (AGn1), 2% (AGn2) in SM, respectively. The results showed that there were no significant differences in weight gain, survival rate, and hepatosomatic index among all groups (P>0.05), while feed coefficient rate in AGn1, AGn2 and TB0.2 groups was significantly lower than that in SM group (P < 0.05). Compared with the PM group, the intestinal inflammation of largemouth bass in SM group were obvious, accompanied by the damage of intestinal structure, the decrease of digestive enzyme activity, and the up-regulation of proinflammatory cytokines. Compared with the SM group, the activities of intestinal trypsin, lipase and foregut amylase in TB and AGn groups increased significantly (P<0.05), and the gene expression levels of acetyl-CoA carboxylase (ACC), caspase-3, caspase-8, caspase-9, tumor necrosis factor alpha (TNF-α), and interleukin-1 beta (IL-1β) were down-regulated, while the gene expression levels of target of rapamycin (TOR) and eIF4E-binding protein (4E-BP) were up-regulated in all experimental groups (P<0.05). It can be concluded that supplementation of 1%-2% AGn and 0.1%-0.2% TB can alleviate enteritis caused by high-level soybean meal, and the recommend level is 2% AGn and 0.2% TB.